Evaluasi Kinerja Program Bina Keluarga Balita (BKB) di Kelompok BKB Mekar Sari 2 Kelurahan Pedurungan Kidul Kecamatan Pedurungan Kota Semarang - Dwi Muhammad Furqon; Kismartini Kismartini; Fathurrohman Fathurrohman (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
Infant’s Family Development (Bina Keluarga Balita/BKB) is part of the Family Planning (Keluarga Berencana/KB) program which aims to improve parents’ and other family members’ knowledge and skills in fostering the growth and development of infants through physical, motor, intellectual, emotional, and socio-economic stimulation as well as possible so as to optimize family functions. The BKB program includes activities such as extension meetings, playing with educational play equipment, and recording the children’s development results on the child development charts (Kartu Kembang Anak/KKA). Data of this research were processed using key performance indicators for government agencies.This research used a qualitative-descriptive method. Research findings were obtained by interviewing the actors involved in the program, including the Semarang city Family Planning, Women and Community Empowerment Agency (Bapermasper & KB), Technical Implementation Unit of Bapermasper & KB (UPTB), and BKB group Mekar Sari 2 in Pedurungan Kidul administrative village, Pedurungan subdistrict, to determine the extension meetings activity and the achievement of the BKB program.From the analysis, it can be concluded that BKB group Mekar Sari 2 still found constraints to cadre training and regeneration as well as BKB Kit disbursement. The level of achievement of the BKB Program for the 2-to-3-year Age Group at BKB group Mekar Sari 2 on the program performance evaluation form (EK-2) fell under the category of “Quite Successful” with the total value of 77.33.